Comparison of Clinical Efficacy and Anatomical Investigation between Retrolaminar Block and Erector Spinae Plane Block - Onishi, Eiko (Biomed Res Int, 2019)
Retrolaminar block (RLB) and erector spinae plane block (ESPB) are alternative approaches to paravertebral block (PVB) and are advantageous in that they are easier and safer techniques compared with the traditional PVB. Many clinical reports of these blocks have described their efficacy for ipsilateral thoracic analgesia. The local anesthetic injection points of RLB and ESPB are the lamina and transverse process, respectively. Despite the similarity of the puncture sites, there have been no clinical studies comparing RLB and ESPB. In addition, the underlying mechanism of these blocks has not been clarified. Recent anatomical investigations indicated that the injectate was distributed in the paravertebral space and spread laterally into the intercostal spaces. The limited distribution into the paravertebral space indicated that compared to PVB, RLB and ESPB exert their effects via a different mechanism. In this review, we describe the features of and differences between RLB and ESPB based on current clinical and anatomical reports. We also propose the clinical indication and discuss the differences, clinical outcomes, and anatomical mechanisms of the techniques.